A large family of Dscam genes with tandemly arrayed 5′ cassettes in Chelicerata - Yuan Yue (Nature Portfolio, 2016)
Drosophila Dscam1 and vertebrate clustered protocadherins (Pcdh) are known for their extraordinary isoform diversity. Here authors identify a shortened Dscam gene family in Chelicerata, which displays homology to Drosophila Dscam1, and employs splicing patterns similar to that of vertebrate Pcdhs.